A Painless Retroauricular Mass in A Patient with Myotonic Dystrophy: Computed Tomographic Documentation of the Bone Changes that Occur in the Skull Base - Som, Peter M. (1997)
A 16-year-old male with a history of neonatal myotonic dystrophy had a painless enlarging left retroauricular mass. Computed tomography showed an enlarged frontal sinus, thickened apparently normal bone in the anterior left clinoid process, doresum sellae, and all portions of the temporal bones. In particular, there was bone production in the left retroauricular region and along the margins of the left internal auditory canal. The left temporomandibular joint was also dislocated. This is the first case report to document the dynamic aspect of the bone changes in this dystrophy.